Figs Fruit Act as Adequate Anti-Inflammatory Agents against Injured Intestines and Memory Impairment of Acute Hypoxia-Induced Rats - Naurasarah, Zhafira; Meliala, Andreanyta; Supriyanto, Irwan; Onky Silvana Wijaya, Yogik; Narwidina, Paramita; Emmanuela Selamat, Claire; Kaila Priandika, Rangga (Journal of Food and Pharmaceutical Sciences, 2025)
Acute hypoxia (AH) may induce inflammation, increase reactive oxygen species (ROS) production, and play an important role in disrupting mucosal integrity and memory impairment through the gut-brain axis. As such, this study aimed to investigate the protective effects of Ficus carica puree (FCP) in rats with AH (10% O2, 90% N2, 4h) - induced intestinal injury. Thirty male Sprague-Dawley rats were divided into 6 groups: NC (negative control, untreated), PC (positive control), VC (vehicle, treated with corn oil), and FC1, FC2, and FC3 (FC1, 2, and 4 mL of FCP/200g). Histopathological analysis of the ileum, the levels of nitric oxide (NO), and tumor necrosis factor-α (TNF-α) were measured in plasma, and the novel object recognition (NORT) was used as a behavior test. The ileal tissues of FC1, FC2, and FC3 groups showed fewer inflammatory cells and less tissue damage than the NC group. The FCP exhibited non-dose-dependent anti-inflammation activity in TNF-α, NO, IL-6 levels, and histopathological analysis. Rats receiving all doses of FCP spent more time exploring the new object in NORT, suggesting the benefits of the phenolic compounds in Ficus carica as a functional food in alleviating the inflammatory and oxidative impacts of AH-induced intestinal injury.